Penerapan Gesture Recognition Pada Aplikasi Desktop Komputer Sebagai Sarana Pengembangan Ketrampilan Penggunaan Mouse (Studi Kasus : SD Mataram Semarang) - Ambarwati Subiyanto, Ema; - STMIK Provisi Semarang, Fitro Nur Hakim (APMMI - Asosiasi Profesi Multimedia Indonesia, 2018)
Abstract - Gesture is a development of HCI (Human Computer Interface), a very simple feature that allows users to operate a smartphone. Gesture is now known to many people, gesture is a feature of the smartphone is very interesting, if Gesture can be applied to the field of education, will be very interesting students to learn to know the computer. Gesture-based applications can maximize the ability of a mouse on a desktop computer without the need for additional facilities. Keywords : gesture; recognition; desktop; mouse Abstract - Gesture is a development of HCI (Human Computer Interface), a very simple feature that allows users to operate a smartphone. Gesture is now known to many people, gesture is a feature of the smartphone is very interesting, if Gesture can be applied to the field of education, will be very interesting students to learn to know the computer. Gesture-based applications can maximize the ability of a mouse on a desktop computer without the need for additional facilities. Keywords : gesture; recognition; desktop; mouse